2021
DOI: 10.1016/j.jdeveco.2021.102626
|View full text |Cite
|
Sign up to set email alerts
|

Contract farming and rural transformation: Evidence from a field experiment in Benin

Abstract: In recent decades contract farming has emerged as a popular mechanism to encourage vertical coordination in developing country agriculture. The goal of such coordination is to better integrate smallholder farmers into the modern agricultural food system, fostering rural transformation. We use panel data from a randomized control trial to quantify the impact of different contract attributes on rural transformation and welfare of smallholder rice farmers in Benin. We vary the terms of contract, with some farmers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 58 publications
2
31
0
Order By: Relevance
“…Since we are estimating associations between digital extension services and several outcome variables, it is possible that some significant results occur simply due to chance meaning that false positives may be an issue. To address this potential issue when testing multiple hypotheses, we follow Arouna et al [ 53 ] and present p -values corrected for the family-wise error rate (FWER), which is the probability of making at least one false discovery among a family of comparison, using the Bonferroni correction and Holm [ 54 ] adjusted p -values (see S4 Table in the supporting information). For our main results, we also present sharpened q -values adjusted for multiple hypotheses testing [ 55 ].…”
Section: Econometric Approachmentioning
confidence: 99%
“…Since we are estimating associations between digital extension services and several outcome variables, it is possible that some significant results occur simply due to chance meaning that false positives may be an issue. To address this potential issue when testing multiple hypotheses, we follow Arouna et al [ 53 ] and present p -values corrected for the family-wise error rate (FWER), which is the probability of making at least one false discovery among a family of comparison, using the Bonferroni correction and Holm [ 54 ] adjusted p -values (see S4 Table in the supporting information). For our main results, we also present sharpened q -values adjusted for multiple hypotheses testing [ 55 ].…”
Section: Econometric Approachmentioning
confidence: 99%
“…LSLAs may also deliver benefits through contract farming, where those who gain control over land (often companies) act as buyers of crops grown by local farmers under contracts specifying price, quantity and other market specifications (Bellemare andLim 2018, Agrawal et al 2019). Outside the context of LSLAs, contract farming programs can improve smallholder farmer incomes and welfare under a variety of contract conditions (Bellemare 2012, Ton et al 2018, Arouna et al 2021, although concerns related to unequal access remain (Sulle 2017, Isager et al 2018, Martiniello 2021.…”
Section: Introductionmentioning
confidence: 99%
“…Other market support policies can have a greater impact on providing incentives for farmers to invest in greater crop quantity or quality. Impact evaluations have shown that the certainty provided by sales contracts between farmers and buyers implemented at the beginning of the season can have sizeable productivity impacts without any additional support (Arouna, Michler, and Lokossou 2021). Investments in scales and thirdparty quality certification have also been shown to incentivize productivity investments with net income increases for farmers (Bernard et al 2017;Saenger, Torero, and Qaim 2014).…”
Section: Spending To Address Market Failures Is Often Of Higher Value...mentioning
confidence: 99%